2005
DOI: 10.1177/0963662505048409
|View full text |Cite
|
Sign up to set email alerts
|

Public culture and public understanding of genetics: a focus group study

Abstract: As the role of genetic science in everyday life has grown, policymakers have become concerned about Americans’ understandings of this science. Much effort has been devoted to formal schooling, but less attention has been paid to the role of public culture in shaping public understanding of genetics. Research into public cultural messages about genetics has claimed that the public is likely to adopt problematic accounts, but few studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 75 publications
(98 reference statements)
4
75
1
9
Order By: Relevance
“…Open-ended questions invite participants to engage in a research study and is in agreement with Bates et al (2005) who suggests that the subjects' active participation and interaction in the research study is necessary for future investigations of the public understanding of genetics. These 'other' responses, together with the selection of the choices given on the questionnaire, led to two major overall themes regarding the potential barriers against participation for this population in a genetic research study: (1) the need for more information on genetic research studies, including any risks involved in participation and how participation would be beneficial; and (2) providing more details on the methods used to collect, share and maintain security of the genetic sample.…”
Section: Discussionmentioning
confidence: 53%
“…Open-ended questions invite participants to engage in a research study and is in agreement with Bates et al (2005) who suggests that the subjects' active participation and interaction in the research study is necessary for future investigations of the public understanding of genetics. These 'other' responses, together with the selection of the choices given on the questionnaire, led to two major overall themes regarding the potential barriers against participation for this population in a genetic research study: (1) the need for more information on genetic research studies, including any risks involved in participation and how participation would be beneficial; and (2) providing more details on the methods used to collect, share and maintain security of the genetic sample.…”
Section: Discussionmentioning
confidence: 53%
“…The similarity of responses lends support to the assertion by Petersen (2001) that the media coverage in this area is likely "to exert a powerful influence on public responses". However, previous focus group research (Bates, 2005) and the research reported here present a more complex picture of the use by members of the public of the resources provided through the media (Condit, 1999). Commonalties may reflect the media being well attuned to the nature of public beliefs/feelings in this area and reflecting these in the coverage or of both the media and the public drawing on common sources of public discourse in this field.…”
Section: Discussionmentioning
confidence: 75%
“…For example, while there was substantial coverage of therapeutic cloning in the media this was not picked up in the focus groups until the topic was expressly introduced by the researchers. Also the examination of the media showed a range of views presented often within the same newspaper, and so a simple transmission of views from the media to the public is not really viable (cf Bates, 2005;Condit, 1999). Rather members of the public appear to draw upon the media and other public discourse but their views will be influenced by other factors such as more general attitudes and also by interactions with others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of focus groups (Krueger 2004) was selected as it enables to observe the attitudes, beliefs, and reactions of a group in a way that would not be possible using other methods (Gibbs 1997;Krueger 2004;Bates 2005). Thus, the researcher receives lots of information in a short period of time.…”
Section: Methodsmentioning
confidence: 99%